2017
DOI: 10.1017/s1041610217002745
|View full text |Cite
|
Sign up to set email alerts
|

Association between the use of benzodiazepines and opioids with the risk of falls and hip fractures in older adults

Abstract: People who are taking opioids and benzodiazepines have increased risk for hip fracture in Colombia. Strategies to educate physicians regarding the pharmacology of older adults should be strengthened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
2
33
0
1
Order By: Relevance
“…Moreover, we observed an association among opioids, antidepressants, antipsychotics and fractures. These findings are in line with previous studies in a general population and linked to the sedative effects that are specific to this class of drugs again increasing the risk of falls 30‐32 . Prolonged intake of steroids is a well‐established risk factor for osteoporosis by inhibition of osteogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we observed an association among opioids, antidepressants, antipsychotics and fractures. These findings are in line with previous studies in a general population and linked to the sedative effects that are specific to this class of drugs again increasing the risk of falls 30‐32 . Prolonged intake of steroids is a well‐established risk factor for osteoporosis by inhibition of osteogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…The use of opioids is related to adverse reactions such as confusion, hallucinations, delirium or sedation and therefore may be associated with an increased risk of falls [24]. In Colombia, it was found that the use of opioids (OR: 4.49, 95% CI: 2.72-7.42) was significantly associated with an increased risk of suffering a fall and presenting a hip fracture [25], which could happen with the opioids prescribed to hospital discharge, generating greater morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use of potentially inappropriate medications (i.e. benzodiazepines, antipsychotics, antidepressants) may be the cause of increased fall risk (35,36). While some studies denoted independent relation between falls and insomnia (18,36), more studies denoted that the relation between falls and insomnia revealed nonsignificant after adjustment with potential confounders (18,37).…”
Section: Discussionmentioning
confidence: 99%